Urate dysregulation (hyperuricemia and gout) among people living with HIV: A protocol for a systematic review and meta-analysis - Ivaan Pitua; Kim Andrew Otto; Kiragga Denis Lwembawo; Kaweesi Calvin Nantalaga; Maria Gabriella Nampiinga; Michael Ndyomugabe; James Nelson Okema (PLoS ONE, 2026)
Introduction Approximately 39.9 million people are living with HIV worldwide, most in sub-Saharan Africa. Effective antiretroviral therapy has shifted attention to metabolic comorbidities, and emerging evidence links integrase inhibitors such as dolutegravir to elevated serum uric acid, yet the global burden of hyperuricemia and gout in this population is unquantified. Methods and analysis This protocol describes a systematic review and meta-analysis of observational studies (cross-sectional, cohort, and case-control) published from inception to May 2026. We will search PubMed/MEDLINE, EMBASE, Web of Science, and CINAHL. Studies involving adults (≥18 years) living with HIV that report the prevalence or incidence of hyperuricemia or gout will be included. Two independent reviewers will screen studies, extract data, and assess risk of bias using the Joanna Briggs Institute Prevalence Critical Appraisal Checklist and the Newcastle-Ottawa Scale (NOS). Primary outcomes are the pooled prevalence of hyperuricemia and gout in PLHIV. Secondary outcomes include risk factors associated with urate dysregulation (ART regimen, Cluster of Differentiation 4 [CD4] count, viral load, metabolic comorbidities, and HIV duration), and gout as an immune reconstitution inflammatory syndrome (IRIS) manifestation. A random-effects meta-analysis using the DerSimonian-Laird method with Freeman-Tukey double-arcsine transformation for prevalence data will be performed in R software. Heterogeneity will be assessed using the I 2 statistic and Cochran’s Q test. Subgroup analyses will explore variation by ART class (pre-ART, PI, NNRTI, INSTI/dolutegravir era), geographic region, CD4 category, and study quality. PROSPERO Registration Number CRD420261360734.